2015
DOI: 10.1121/1.4932165
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic properties of vowel production in prelingually deafened Mandarin-speaking children with cochlear implants

Abstract: The present study examined the acoustic features of vowel production in Mandarin-speaking children with cochlear implants (CIs). The subjects included 14 native Mandarin-speaking, prelingually deafened children with CIs (2.9-8.3 yr old) and 60 age-matched, normal-hearing (NH) children (3.1-9.0 years old). Each subject produced a list of monosyllables containing seven Mandarin vowels: [i, a, u, y, ɤ, ʅ, ɿ]. Midpoint F1 and F2 of each vowel token were extracted and normalized to eliminate the effects of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…Consistent with previous studies [15,39], the present study showed that the CI children produced all compound vowels with longer duration than the NH peers, which suggested that the CI children may need more time to form the articulatory gestures and to travel from one target to the other. Earlier research on NH speakers reported that lengthened vowel duration and greater formant frequency change corresponded to higher speech clarity [40].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous studies [15,39], the present study showed that the CI children produced all compound vowels with longer duration than the NH peers, which suggested that the CI children may need more time to form the articulatory gestures and to travel from one target to the other. Earlier research on NH speakers reported that lengthened vowel duration and greater formant frequency change corresponded to higher speech clarity [40].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the comparison of relative position defined by F1 and F2 between the NH and CI children, a measure of overall acoustic distance was calculated to show the potential positional deviation of the CI children relative to NH targets. Following the procedure described in Yang et al [15], for each vowel, the mean F1 and F2 were calculated for each measurement point in the NH children. Then, the Euclidean distance between each participant and the NH target was calculated for each measurement point.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the F1 and F2 values were converted to their respective z-scores following the Lobanov's method (Lobanov, 1971). The zscores were then rescaled back to Hz-like values following Thomas and Kindle (2007) to facilitate comparison and interpretation (see also Yang et al, 2015).…”
Section: Acoustic Measurementsmentioning
confidence: 99%